The Power of Data Analytics in Decision-Making - Musinov Dilshod Sultonovich; Ravshanov Yodgor Fayzi oʻg‘li; Xoʻrozov Asadbek Olimjon oʻg‘li (Academia One, 2024)
In today's data-driven business landscape, the power of data analytics in decision-making cannot be overstated. This article explores the significance of data analytics in facilitating informed decision-making processes across various industries and organizational functions. Through an examination of case studies, best practices, and emerging trends, it highlights the transformative impact of data analytics on improving business performance, driving innovation, and gaining competitive advantage. From descriptive and diagnostic analytics to predictive and prescriptive analytics, different types of data analytics techniques are leveraged to extract valuable insights from data and guide strategic decision-making. Additionally, this article discusses the challenges and opportunities associated with implementing data analytics initiatives, emphasizing the importance of data governance, talent development, and organizational culture in maximizing the benefits of datadriven decision-making.
Keywords: data analytics; decision-making; big data